Perkembangan Ekonomi Islam dari Masa Nabi Muhammmad SAW Hingga Era Keuangan Syariah Modern - Putri Ayu Manalu; Syarifah Khairatun Hisan; Nazwa Tantri Fitria; Ahmad Wahyudi Zein (Jurnal Pajak dan Analisis Ekonomi Syariah, 2024)
Understanding the life journey of the Prophet Muhammad SAW is the core of the history of the development of Islamic economics. Islamic economics is characterized by the principles of justice, transparency, and the prohibition of usury. After that, the development of Islamic economics continued through various dynasties and civilizations, which integrated Islamic values into trade and investment practices. This study intends to examine the factors that contributed to the development of Islamic economics and its place in the contemporary global economic system. The economic system from the time of the Prophet Muhammad to the current Islamic finance era is examined. The rise of Islamic financial institutions and financial products that adhere to Islamic law in the modern era demonstrates how Islamic economics has adapted to the challenges of the times.